Modeling the polyphenoloxidase inactivation kinetics in pear, apple and strawberry purees after high pressure processing - Sulaiman, A.; Soo, M.J.; Yoon, M.M.L.; Farid, M.; Silva, F.V.M. (2015)
High Pressure Processing of Royal Gala apple, Taylor's Gold pear and Camarosa strawberry purees was carried out to inactivate polyphenoloxidase (PPO). First, 600 MPa enzyme inactivation at room temperature was investigated. After 60 min, strawberry (8 RA, residual activity) and apple (89 RA) PPOs were partially inactivated and pear PPO was not inactivated, demonstrating the high variability in the resistance of different fruits' PPOs. Then, the fruit purees were submitted to 600 MPa combined with mild heat, and the PPO inactivation kinetics was modeled. The pear PPO was found to be resistant even after 60 min 600 MPa-71 degrees C process. Regarding apple and strawberry PPOs, 600 MPa-thermal inactivation of PPO followed a biphasic first order kinetics exhibiting stable and labile fractions. The k(s) values (rate constant for stable fraction) at 57 degrees C and 71 degrees C were 0.0121 min(-1) and 0.0184 min(-1) for apple PPO, and 0.0182 min(-1) and 0.0805 min(-1) for strawberry PPO. (C) 2014 Elsevier Ltd. All rights reserved.